2022
DOI: 10.1111/cns.13870
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term functional prognosis and related factors of spinal cord stimulation in patients with disorders of consciousness

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Subsequently, DellaPepa et al summarized multiple SCS studies and found that 51.6% patients with pDOC showed recovery of consciousness and inferred the treatment effect is that SCS activates the thalamocortical pathway and increases cerebral blood flow through the ascending reticular activating system (12). Our research team also reported that 31.8% patients showed improvement in consciousness (6), and the above findings suggest that SCS can effectively promote the recovery of consciousness. The overall effective rate of SCS ranges from 20 to 40% (13).…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Subsequently, DellaPepa et al summarized multiple SCS studies and found that 51.6% patients with pDOC showed recovery of consciousness and inferred the treatment effect is that SCS activates the thalamocortical pathway and increases cerebral blood flow through the ascending reticular activating system (12). Our research team also reported that 31.8% patients showed improvement in consciousness (6), and the above findings suggest that SCS can effectively promote the recovery of consciousness. The overall effective rate of SCS ranges from 20 to 40% (13).…”
Section: Introductionsupporting
confidence: 62%
“…To verify the effectiveness of st-SCS and exclude the interference of natural recovery as much as possible, the study chose the same time of enrollment (3 months after onset brain injury) as conventional SCS (6,15). And, we adopted a selfcontrolled design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for surgical procedures, a C5 vertebra laminotomy is made and the electrode array is delivered up to the target zone at the midline of the C2–C5 level ( 12 ), and the electrode position may affect prognosis and patient tolerance. We preliminary reported stimulation parameters that could affect the therapeutic effects of SCS, such as inter-stimulus interval and frequency ( 5 , 13 ), and summarized clinical characteristics on patients' outcomes ( 14 ). Considering that the mechanism of SCS to treat disturbance of consciousness possibly underlying in the direct stimulation of the dorsal column, and since we observed that patients with electrodes closer to the midline seem to have a better prognosis, we proposed that surgical factors such as electrode deviation may affect the outcomes of patients.…”
Section: Introductionmentioning
confidence: 99%